Hepatitis B pada Kehamilan: Strategi Pengabdian Masyarakat untuk Pencegahan dan Penanganan - Moelyadi, Felly; Saraswati, Faizah Alda; Bulandaru, Favan Maulana; Husodo, Febrianto Adi; Samudra, Ferizal Negeri (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Hepatitis B remains a major global health issue, particularly in pregnancy due to the high risk of vertical transmission from mother to baby. This type of transmission is a leading cause of chronic infection in infants and may result in long-term health consequences. This community engagement program was conducted at Haji General Hospital Surabaya to increase awareness among pregnant women and their families regarding the prevention, early detection, and management of Hepatitis B during pregnancy. The program utilized interactive educational methods, including presentations, the distribution of informative leaflets, and question-and-answer sessions. Participants’ knowledge was assessed before and after the sessions. Results demonstrated a significant increase in participants’ understanding of the definition, transmission modes, symptoms, and risk factors, as well as preventive and management strategies related to Hepatitis B in pregnancy. This initiative had a positive impact on raising awareness about the importance of screening, vaccination, and other preventive measures to reduce the risk of infection in pregnant women and their newborns. Such programs are expected to be carried out regularly to effectively lower the rate of perinatal Hepatitis B transmission in the community.